BIOCHEMICAL INDICATORS OF MILITARY BLOOD ON THE ISCHEMIC AND DENERVATION PROCESS IN MUSCLES AFTER A MINE-EXPLOSIVE INJURYS - Magomedov, Sadrudin; Polyachenko, Yurii; Dolhopolov, Oleksii; Kostrub Оlexandr; Litovka, Iryna; Rohozynskyi, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The injuries received are accompanied by massive damage to the soft tissues of the limbs, main vessels and nerves, and the development of compartment syndrome. Violation of muscle function in the case of a limb injury can be both a consequence of denervation — as a result of damage to peripheral nerves, and ischemia with subsequent necrosis and fibrosis — as a result of direct or indirect damage to muscles, «tenotomy syndrome» — in case of traumatic damage to tendons and muscles yams, with the simultaneous combination of denervation and ischemia. Markers for assessing the state of muscle tissue — levels of Na+, K+ and Ca++ electrolytes, indicators of kidney function (urea, creatinine); glucose and the products of its transformations — lactate (lacticacid) and pyruvate (pyruvic acid) and, finally, muscle enzymes, namely creatine kinase (CK) and lactate dehydrogenase (LDH). Objective. To study the biochemical indicators of blood (activity of energy metabolism enzymes and electrolyte content) of military personnel with ischemic contracture and muscle denervation after a mine-explosive injury. Methods. The blood serum of 45 people, who were divided into IV groups, was analyzed. The average age of patients of the II group was 33.75 ± 3.46; III — 37 ± 3.66; IV — 35.86 ± 2.35. The results. The activity of LDH and CK and the content of electrolytes Na+, K+, Ca++ were determined in blood serum. Conclusions. LDH plays a key role in lactate metabolism and maintenance of energy balance in skeletal muscle. Its increased activity indicates the presence of hypoxia due to ischemic contracture of the limb and damage to peripheral nerves. KK enzyme protects cell membranes from damage. The tendency to decrease the activity of CC is a negative sign that reflects the initial process of destruction of the cell membranes of muscles damaged by a mine-explosive injury. The obtained results can be used to determine the severity of pathological processes in patients after traumatic damage to peripheral nerves and ischemic contracture, as well as when assessing the expediency of surgical intervention.